EVALUATION OF NUCLEAR CHANGES IN THE BUCCAL EPITHELIAL CELLS OF TOBACCO USERS IN NNEWI, SOUTH EAST NIGERIA - SAMUEL IFEDIORANMA OGENYI; ANTHONY AJULUCHUKWUNGOKERE; JONATHAN MADUKWE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to evaluate nuclear changes in the buccal epithelial cells of commercial bus drivers using tobacco in Nnewi. Tobacco use constitutes a major risk factor of oral lesions, due to its genotoxic and mutagenic effects on the buccal cavity epithelial cells. Methods: One hundred and twenty-three subjects, consisting of 83 tobacco users (test group) and 40 tobacco and alcohol non-users (control group) were recruited for this cross-sectional study. Buccal smear was obtained from each participant, processed, and stained with the Papanicolaou staining method. Two hundred cells were counted for each stained slide and the percentage of various nuclear changes determined, and the repair index calculated. Comparisons of nuclear changes between and within groups were carried out using the Kruskal–Wallis H-test with p<0.05 considered significant. Results: Micronuclei were the most prevalent nuclear changes (100%) while broken egg nuclei were the least (15.2%). Nuclear changes were most prevalent among snuffers (33.42%). A statistically significant difference (p˂0.05) was observed when the median values of nuclear changes were compared in different study groups and control subjects. Similarly, the prevalence of nuclear changes increased with the age of subjects and the duration of tobacco use, whereas the repair index decreased with increased prevalence. Conclusion: Increased nuclear changes were observed in the buccal epithelial cells of tobacco users, with snuff inhalation slightly impacting more severe effects than cigarette smoking. Buccal smear cytology may constitute an effective screening method for precancerous lesions amongst tobacco users.